COGNITIVE COMPETENCE AND ITS PLACE IN THE TEACHING OF THE TAJIK LANGUAGE (Scientific journal of the Fergana State University, 2023)
This article discusses the issue of teaching the Tajik language by non-traditional methods in the 10th grade of secondary schools when studying complex topics based on textbooks and other necessary educational materials.